THE EFFECT OF FLOW RATE AND CURRENT ON CONE JET MORPHOLOGY AND ITS APPLICATION TO CONTROL FIBER DIAMETER IN CONSTANT-CURRENT ELECTROSPINNING - William Wijaya, Kelvin
Nanofiber technology is a technology that is currently developing rapidly. One of these technology is the electrospinning method. Electrospinning is a method of fabricating fibers that are versatile and simple so that they are widely used. In this Final Project, the synthesis of Polyvinyl pyrrolidone (PVP) fibers is carried out to determine the relation of morphology of the cone jet and the diameter of the fiber to the current and flow rate of the solution. Preparation of two PVP solutions using ethanol and Dimethyl formamide (DMF) as a solvent with a composition of 15% and 18% dissolved weight and 1: 1 solvent weight composition. The solution is then used in electrospinning to produce fibers. Current variations and flow rates are carried out in the process of fiber synthesis. The synthesized fiber is then observed under a microscope. The results show that the distribution of fiber diameter will increase with increasing flow rate. While the distribution of fiber diameter will decrease in the current variation when the current increases. During the synthesis process, the cone jet image is taken using a camera to be analyzed. In this image, the size of the cone jet will be greater as the current increases so that the jet length will decrease. Meanwhile, size of the cone jet will be lesser as the flow rate increases so that the jet length will increase. There is a limitation in the model used where the diameter of the cone jet must be equal to the diameter of the syringe to produce a stable jet. Then, the graph of cone jet length to current and flow rate shows that there is a polynomial relationship between the three variables. Then, the graph of cone jet length to the cone jet volume shows a quadratic relationship. In addition, the graph also shows that the diameter of the fiber and the length of the cone jet have a polynomial relationship. Thus, the flow rate and current can be controlled to produce a good cone jet morphology so that the fiber diameter can be controlled.